Evidence for increased olfactory receptor gene repertoire size in two nocturnal bird species with well-developed olfactory ability - Steiger, Silke S (BioMed Central, 2009)
BACKGROUND: In vertebrates, the molecular basis of the sense of smell is encoded by members of a large gene family, namely olfactory receptor (OR) genes. Both the total number of OR genes and the proportion of intact OR genes in a genome may indicate the importance of the sense of smell for an animal. There is behavioral, physiological, and anatomical evidence that some bird species, in particular nocturnal birds, have a well developed sense of smell. Therefore, we hypothesized that nocturnal birds with good olfactory abilities have evolved (i) more OR genes and (ii) more intact OR genes than closely related and presumably less 'olfaction-dependent' day-active avian taxa. RESULTS: We used both non-radioactive Southern hybridization and PCR with degenerate primers to investigate whether two nocturnal bird species that are known to rely on olfactory cues, the brown kiwi (Apteryx australis) and the kakapo (Strigops habroptilus), have evolved a larger OR gene repertoire than their day-active, closest living relatives (for kiwi the emu Dromaius novaehollandiae, rhea Rhea americana, and ostrich Struthio camelus and for kakapo the kaka Nestor meridionalis and kea Nestor notabilis). We show that the nocturnal birds did not have a significantly higher proportion of intact OR genes. However, the estimated total number of OR genes was larger in the two nocturnal birds than in their relatives. CONCLUSION: Our results suggest that ecological niche adaptations such as daily activity patterns may have shaped avian OR gene repertoires.